Current State of Dendritic Cell-Based Immunotherapy: Opportunities for in vitro Antigen Loading of Different DC Subsets? - Huber, Anne; Dammeijer, Floris; Aerts, Joachim G. J. V.; Vroman, Heleen (Frontiers in Immunology, 2018)
Dendritic cell (DC) based cancer immunotherapy aims at the activation of the immune system, and in particular tumor-specific cytotoxic T lymphocytes (CTLs) to eradicate the tumor. DCs represent a heterogeneous cell population, including conventional DCs (cDCs), consisting of cDC1s and cDC2s, plasmacytoid DCs (pDCs), and monocyte-derived DCs (moDCs). These DC subsets differ both in ontogeny and functional properties, such as the capacity to induce CD4+ and CD8+ T-cell activation. MoDCs are most frequently used for vaccination purposes, based on technical aspects such as availability and in vitro expansion. However, whether moDCs are superior over other DC subsets in inducing anti tumor immune responses, is unknown, and likely depends on tumor type and composition of the tumor microenvironment. In this review, we discuss cellular aspects essential for DC vaccination efficacy, and the most recent findings on different DC subsets that could be used for DC-based cancer immunotherapy. This can prove valuable for the future design of more effective DC vaccines by choosing different DC subsets, and sheds light on the working mechanism of DC immunotherapy.